Near-Infrared Quantum Dots as Optical Probes for Tumor Imaging - Gao, Jinhao (2010)
Molecular imaging plays a key role in personalized medicine, which is the goal and future of patient management. Among the various molecular imaging modalities, optical imaging may be the fastest growing area for bioanalysis, and the major reason is the research on fluorescence semiconductor quantum dots (QDs) and dyes have evolved over the past two decades. The great efforts on the synthesis of QDs with fluorescence emission from UV to near-infrared (NIR) regions speed up the studies of QDs as optical probes for in vitro and in vivo molecular imaging. For in vivo applications, the fluorescent emission wavelength ideally should be in a region of the spectrum where blood and tissue absorb minimally and tissue penetration reach maximally, which is NIR region (typically 700–1000 nm). The goal of this review is to provide readers the basics of NIR-emitting QDs, the bioconjugate chemistry of QDs, and their applications for diagnostic tumor imaging. We will also discuss the benefits, challenges, limitations, perspective, and the future scope of NIR-emitting QDs for tumor imaging applications.